Protection of Women Labour: An International Perspective (Journal of Advances and Scholarly Researches in Allied Education, 2025)
The protection of women in the workforce is a critical element in achieving gender equality and promoting fair labor practices worldwide. This paper explores the multifaceted approach toward the protection of women labor within an international context, focusing on the frameworks, conventions, and practices established by global organizations such as the International Labour Organization (ILO) and United Nations (UN). Through comparative analysis, this study examines policies implemented in various countries, highlighting best practices, challenges, and gaps. The aim is to present an integrative approach toward strengthening policies that support women's rights and safety in labor, especially in vulnerable sectors.